The Kentucky fresh cookbook - Green, Maggie (University Press of Kentucky, 2011)
A seasonal food journey with native Kentuckian Maggie Green, The Kentucky Fresh Cookbook takes home chefs through a year in a Kentucky kitchen with more than 200 recipes. With a focus on the cook's activities in the kitchen, this book guides both aspiring and experienced cooks in the preparation of delicious meals using the delightful variety of foods found in Kentucky. Green welcomes readers with her modern and accessible approach, incorporating seasonally available Kentucky produce in her recipes but also substituting frozen or canned food when necessary. She complements her year of recipes w.